Exploring career interest and STEM self-efficacy: implications for promoting gender equity - Yamani, Niam; Almazroa, Hiya (Frontiers in Psychology, 2024)
This study explores the relationship between career interests and self-efficacy in Science, Technology, Engineering, and Mathematics (STEM) among young girls in Riyadh, Saudi Arabia. Employing a quantitative research design with a correlational approach, we utilize the S-STEM survey to measure changes in students' STEM subject efficacy and their interest in STEM careers. Our sample comprises 671 middle and high school female students from 49 schools, representing a diverse cross-section of the population. The findings indicate that female students exhibit high levels of STEM self-efficacy and have a strong preference for medicine as a career choice. While the overall interest in STEM careers among students is moderate, there are notable variations in interest across different STEM fields. Importantly, a positive and significant correlation was observed between female students' interest in STEM careers and their self-efficacy in STEM. This research holds important implications for the promotion of STEM education and careers among female students. By recognizing the unique context of Saudi Arabia and the perspectives of young girls in Riyadh, this study offers a fresh perspective on the factors influencing STEM career aspirations and highlights the importance of fostering self-efficacy beliefs among female students.